PENINGKATAN CIVIC ENGAGEMENT SISWA MELALUI E-PLATFORM CIVICITA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA - Sidiqah, Nurul; Rahmat; Nisrina Nurul Insani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to measure the effect of the CIVICITA E-Platform on increasing civic engagement among 11th grade students at Darmayanti Cimaung High School in Pancasila Education. The method used is a quasi-experiment with a pretest-posttest non-equivalent control group design, involving 68 students divided into an experimental class and a control class. Data were collected through essay tests and observations. The Paired Samples t-Test results showed a significance value of p = 0.000 (p < 0.05), which means that there was a significant difference between the pretest and posttest scores of the experimental class. The average N-Gain of the experimental class was 0.54 (medium category), far exceeding that of the control class, which was 0.13 (low category). Cohen's d value of 2.350 indicates a very large practical effect. The observation results show that the civic engagement score reached 99/100 (very high category). These findings show that the CIVICITA E-Platform is effective in increasing students' active participation and civic awareness through interactive, contextual, and real social action-based learning.